ROLE OF THERAPEUTIC HYPOTHERMIA IN IMPROVING OUTCOME AFTER TRAUMATIC BRAIN INJURY : A SYSTEMATIC REVIEW - Roberto Pratama, Joshua (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: A nondegenerative and noncongenital brain injury caused by external mechanical forces can cause permanent or temporary harm to cognitive, physical, and psychosocial functions and change or diminish awareness. Traumatic brain injury can cause cerebral edema and ICP increase, worsening the lesion. Cellular death can occur minutes to hours after an injury, although negative effects can last 72 hours or more. Therapeutic hypothermia (HT) can lower ICP and protect neurons, improving patient prognosis and lowering mortality. The aim: This article showed role of therapeutic hypothermia in improving outcome after traumatic brain injury. Methods: This study demonstrated compliance with all requirements by comparing itself to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 standards. Therefore, the experts were able to ensure that the study was as current as feasible. For this search strategy, publications published between 2013 and 2023 were considered. Several online reference sources, including Pubmed and SagePub, were utilized for this purpose. It was determined not to consider review pieces, previously published works, or works that were only partially completed. Result: In the PubMed database, the results of our search brought up 112 articles, whereas the results of our search on SagePub brought up 107 articles. The results of the search conducted for the last year of 2013 yielded a total 59 articles for PubMed and 38 articles for SagePub. In the end, we compiled a total of 28 papers, 19 of which came from PubMed and nine of which came from SagePub. We included seven study that met the criteria. Conclusion: HT has not reduced, but may have increased, mortality in TBI patients in some high-quality studies. However, TBI patients with elevated ICP may benefit from hypothermia as therapy rather than as prophylaxis when initiated within 24 hours.